Breastfeeding training for health professionals and resultant changes in breastfeeding duration - Taddei, José Augusto de Aguiar Carrazedo; Westphal, Marcia Faria; Venancio, Sonia; Bogus, Cláudia; Souza, Sonia (São Paulo Medical Journal, 2000)
CONTEXT: Promotion of breastfeeding in Brazilian maternity hospitals. OBJECTIVE: To quantify changes in the breastfeeding duration among mothers served by hospitals exposed to the Wellstart-SLC course, comparing them with changes among mothers attended by institutions not exposed to this course. DESIGN: Randomized Institutional Trial. SETTING: The effects of training on breastfeeding duration was assessed in eight Brazilian hospitals assigned at random to either an exposed group (staff attending the Wellstart-SLC course) or a control group. SAMPLE: For each of the eight study hospitals, two cohorts of about 50 children were visited at home at one and six months after birth. The first cohort (n = 494) was composed of babies born in the month prior to exposure to the Wellstart-SLC course, and the second cohort (n = 476) was composed of babies born six months subsequent to this exposure. MAIN MEASUREMENTS: Kaplan-Meier curves were plotted to describe the weaning process and log-rank tests were used to assess statistical differences among survival curves. Hazard ratio (HR) estimates were calculated by fitting Cox proportional hazard regression models to the data. RESULTS: The increases in estimated, adjusted rates for children born in hospitals with trained personnel were 29% (HR = 0.71) and 20% (HR = 0.80) for exclusive and full breastfeeding, respectively. No changes were identified for total breastfeeding. CONCLUSION: This randomized trial supports a growing body of evidence that training hospital health professionals in breastfeeding promotion and protection results in an increase in breastfeeding duration.